2020
DOI: 10.3390/foods9020247
|View full text |Cite
|
Sign up to set email alerts
|

How Far is the Spanish Snack Sector from Meeting the Acrylamide Regulation 2017/2158?

Abstract: In 2017, the European Commission published Regulation 2017/2158 establishing mitigation measures and benchmark levels to reduce acrylamide in foods. Acrylamide was determined in seventy potato crisp samples commercialized in Spain. The aim was to update knowledge about the global situation in the snack sector and evaluate the effectiveness of mitigation strategies applied, especially since the publication of the Regulation. Results were compared with data previously published in 2004, 2008, and 2014, assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
(41 reference statements)
1
13
0
Order By: Relevance
“…Mesias et al. (2020) analyzed 70 samples of PC commercialized in Spain and also reported higher values of AA, ranging between LOQ and 1930 µg/kg, with a mean content of 644 ± 387 µg/kg. The results were a little higher than the ones previously found in 2014 for PC by the same research team who reported an average AA level of 630 ± 412 µg/kg (Mesias & Morales, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Mesias et al. (2020) analyzed 70 samples of PC commercialized in Spain and also reported higher values of AA, ranging between LOQ and 1930 µg/kg, with a mean content of 644 ± 387 µg/kg. The results were a little higher than the ones previously found in 2014 for PC by the same research team who reported an average AA level of 630 ± 412 µg/kg (Mesias & Morales, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This period was characterised by falls not only in the maximum values of acrylamide, but also in the percentage of samples exceeding the reference value for this food (750 µg/kg). This reduction in acrylamide levels in crisps appears to be due to stricter attention to the temperature and duration of the cooking, blanching before frying (the removal of sugars and other soluble metabolites in hot water), vacuum frying, the control of moisture levels in the final product, the selection of appropriate varieties of fresh potatoes, according to their end use, and the careful control of the storage temperature and conditions of the fresh materials, as well as post-frying quality control by reference to the colour of the food [ 42 ]. All of these mitigation measures, together with other recommendations for the food production sector, are compiled and described in the Acrylamide Toolbox [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…As one of the most concerning food pollutants at present, acrylamide is a low molecular weight compound with high polarity and hydrophilicity [1]. Since the discovery of acrylamide in food, many countries have explored strategies for reducing acrylamide in food products [2–5]. The main formation procedure of acrylamide during the thermal processing of foods is the Maillard reaction [3, 6, 7].…”
Section: Introductionmentioning
confidence: 99%